EVALUATING ADSORPTION KINETICS OF ENDOSULFAN ON NATURAL AND SYNTHETIC ADSORBENTS: A COMPARATIVE STUDY - Muhammad Aamer Hussain; Ghulam Murtaza; Muhammad Zia-ur-Rehman; Muhammad Shahid; Sofia Calero (Journal of Animal and Plant Sciences, 2025)
The present study investigates the adsorption of endosulfan from aqueous solutions using various low-cost adsorbents. Adsorption kinetic data were analyzed using different models to determine the most effective adsorbents. In this study, different adsorbents, including sawdust, sugarcane bagasse, corn cob, sawdust biochar, sugarcane bagasse biochar, corn cob biochar, zeolite, montmorillonite, kaolinite, and magnetite, were applied at a rate of 0.02 g L-1. Endosulfan was spiked at concentrations of 0.01, 0.05, 0.1, 0.5, and 1 mg L-1. For kinetic studies, samples were collected at different time intervals (1, 3, 5, 8, 16, and 24 hours). The results revealed that natural zeolites exhibited the highest removal efficiency among all tested materials, with maximum adsorption capacity between 8 and 16 hours. Due to their large surface area, interlayer ions, and surface charge, clay minerals demonstrated a superior adsorption capacity compared to other adsorbents. Among the kinetic models, the pseudo-second-order model best described the adsorption behavior of most adsorbents, except for montmorillonite. Based on the intra-particle diffusion model, Kid values for sawdust, corncob biochar, and montmorillonite were 0.3093, 0.3075, and 0.3067 (mg g-1 s-0.5), respectively. For montmorillonite, the Qe Exp was 1.89 mg g-1, while Qe max predicted by pseudo-first-order and second-order models were 1.93 and 2.02 mg g-1, respectively. The pseudo-first-order model showed a better fit (R2 = 0.977, and R2 = 0.99) confirming the correlation. It is concluded that natural zeolites are the most effective adsorbent for endosulfan removal, with the pseudo-second-order model best describing adsorption kinetics for most materials.
Keywords: Endosulfan; Low-cost adsorbents; Clay minerals; Zeolites; Montmorillonite; Biochar; Chemisorption